Evaluation of Rh-Hemolytic Disease in Neonates and Management with Early Intensive Phototherapy in the Neonatal Intensive Care Unit. (14th June 2019) - Tewari, Vishal Vishnu; Kumar, Ashutosh; Singhal, Amit; Pillai, Nayana; Prakash, Arya; Varghese, Jaya; Kannan, Venkatnarayan
Abstract: Background of the study: In neonates with Rh-hemolytic disease, light emitting diode (LED) phototherapy allows delivery of high spectral irradiance (SI). A linear correlation exists between SI and efficacy of phototherapy with no saturation point. There is scant data on evaluation and early phototherapy using LED units in Rh-hemolytic disease. Objective: This study aimed to describe the hemoglobin (Hb), hematocrit (Hct), total serum bilirubin (TSB), phototherapy parameters and short-term outcomes in neonates with Rh-hemolytic disease. Methodology: Maternal parameters for Rh-isoimmunization were recorded and monitoring of fetal anemia by Doppler ultrasound was done. Early intensive phototherapy within 1 h of birth was initiated for cord blood Hb below 13.6 g/dl and/or TSB greater than 2.8 mg/dl. Results: Fifty Rh positive neonates were enrolled of which 11/50 (22%) received intrauterine transfusions. The maximum TSB remained below 18 mg/dl in 42/50 (84%) of neonates. The mean SI on the trunk was 56.260 ± 8.768 µW/cm 2 /nm and duration of phototherapy was 7 ± 3.29 days (mean ± SD). There was a positive correlation between strength of indirect antiglobulin test and cord blood Hb: correlation coefficient ( r ) = 0.295; direct antiglobulin test and duration of phototherapy: r = 0.331. Early packed red blood cell (PRBC) transfusion was required in 8/50 (16%) neonates while 20/50 (40%) required late transfusions. Conclusion: With a mean SI of 56.260 ± 8.768 µW/cm 2 /nm on the trunk, TSB remained below 18 mg/dl in majority thereby avoiding exchange transfusion. Early or late PRBC transfusion requirement was 1 (1–2) (median ± interquartile range).